The Mediation Effect of Carbon Accounting in Relation to Carbon Risk Management and Carbon Performance of Malaysian Companies - Ong, Tze San; Kasbun, Nur Fatin; Abdul Rahman, Abdul Aziz; Meero, Abdelrhman; Teh, Boon Heng (International Journal of Energy Economics and Policy, 2022)
This paper enhances the knowledge on carbon management among organizations certified by the Malaysian International Organization for Standardization (ISO) 14001. Specifically, the study investigated the impact of carbon risk management on carbon performance through the mediation of carbon accounting. This research adopts a quantitative method with a final sample size of 136 and structural equation modeling (SEM) was employed to analyze the data. The findings suggest that carbon risk management and carbon accounting have a significant positive effect on carbon performance. Notably, carbon accounting exerts a full mediating effect on the relationship between carbon risk management and carbon performance.